Personal characteristics of residents may predict competency improvement. (3rd November 2015) - Park, EunMi; Ha, Patrick K.; Eisele, David W.; Francis, Howard W.; Kim, Young J.
Abstract : Objectives/Hypothesis: We hypothesized that personal characteristics of residents may affect how well competency is attained in a surgical residency. To this end, we examined two concepts of global trait emotional intelligence and learner autonomy profile and their factor relationship with competency outcomes in a residency program in otolaryngology–head and neck surgery. Study Design: A cohort study prospectively gathered competency change scores for 1 year and retrospectively analyzed the factor associations. Methods: We measured two personal characteristics using the Trait Emotional Intelligence Questionnaire‐Short Form and Learner Autonomy Profile‐Short Form between 2013 and 2014 in a tertiary otolaryngology–head and neck residency program. We prospectively examined faculty‐rated resident competency scores monitored in the same time period and correlated the personal attributes with cumulative competency improvement scores. Statistical analyses included factor correlations and univariate regression. Results: With a response rate of 64% (N = 16/25), we identified two statically significant predictors of competency improvement outcome attained by the end of the year. Regression analyses showed that emotionality factor of global trait emotional intelligence ( P = .04) and learner autonomy profile ( P < .01) were significant predictors for the higher improvement of aggregate competency outcome. Conclusions: Personal factors of individual residents can affect their improvement of overall competency. Practicing competency‐based education should, therefore, include assessing individual resident factors as well as teaching clinical knowledge and technical skills. Level of Evidence: NA Laryngoscope, 126:1746–1752, 2016